Keefektifan Konseling Kelompok dengan Teknik Desensitisasi Sistematis dalam Mereduksi Sifat FoMO (Fear of Missing Out) pada Mahasiswa - Tri Anggraini; Zhila Jannati; Bela Janare Putra (Journal of Society Counseling, 2024)
This research is entitled “The Effectiveness of Group Counseling with Systematic Desensitization Techniques in Reducing FoMO (Fear of Missing Out) in Students". This research is motivated by the FoMO phenomenon, namely the feeling of Fear of Missing Out on an important event that other people have, which makes individuals always connected to social media. Therefore, to evercome problems arising from FoMO, group counseling services with systematic desensitization techniques are used. The aim of this research is to determine the effectivenesd of group counseling using systematic desensitization techniques in reducing the nature of FoMO in students. The type of research used is quantitative. The population in this study was 141 people and the sample size was 8 people, because it used a purposive sampling technique. Data collecton in this research was carried out by distributing a psychological scale, and the data analysis techniques used were the T test. The research results showed that the T test results had a significant value (2-tailed) of 0.001, which was smaller than 0.05, meaning that Ha was accepted and H0 is rejected, it can be concluded that the application of group counseling with systematic desensitization techniques is effective in reducing the nature of FoMO in students.